2022
DOI: 10.1155/2022/3862122
|View full text |Cite|
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells Improve Premature Ovarian Failure through Cell Apoptosis of miR-100-5p/NOX4/NLRP3

Abstract: Premature ovarian failure refers to a series of symptoms of perimenopausal hot flashes, night sweats, decreased libido, vaginal dryness, insomnia, reduced menstruation, sparse hair, even amenorrhea, and even infertility before the age of 40 due to the decline of ovarian function. Premature ovarian failure is a common and difficult disease in gynecology. Its prevalence is increasing gradually, and the trend is younger. The aim of this experiment was to elucidate the role of human umbilical cord mesenchymal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The human ovarian granulosa cell line (KGN cells) is a commonly used cell model in the in vitro experiments to study ovarian functions because these cells are easy to isolate, culture, and transfect and can be analyzed by immunocytochemical methods (18,19).KGN cells were cultured at 37°C in 5% CO 2 and 95% air. Dulbecco's modi ed Eagle's medium/nutrient mixture F-12 ham (DMEM/F-12; Sigma Aldrich, USA) was used to culture the cells and supplemented with penicillin (100 U/mL, Invitrogen, life technologies, USA), streptomycin sulfate (100 µ G/mL, Invitrogen, Life Technologies, USA), glutamine (1x, Invitrogen, life technologies, USA), and 10% carbon/dextran treated fetal bovine serum (10%, HyClone, USA).…”
Section: Human Ovarian Granulosa Cell Line (Kgn Cells) Culturementioning
confidence: 99%
“…The human ovarian granulosa cell line (KGN cells) is a commonly used cell model in the in vitro experiments to study ovarian functions because these cells are easy to isolate, culture, and transfect and can be analyzed by immunocytochemical methods (18,19).KGN cells were cultured at 37°C in 5% CO 2 and 95% air. Dulbecco's modi ed Eagle's medium/nutrient mixture F-12 ham (DMEM/F-12; Sigma Aldrich, USA) was used to culture the cells and supplemented with penicillin (100 U/mL, Invitrogen, life technologies, USA), streptomycin sulfate (100 µ G/mL, Invitrogen, Life Technologies, USA), glutamine (1x, Invitrogen, life technologies, USA), and 10% carbon/dextran treated fetal bovine serum (10%, HyClone, USA).…”
Section: Human Ovarian Granulosa Cell Line (Kgn Cells) Culturementioning
confidence: 99%
“…HUCMSCs exosomal miRNA-100-5p has acted through the NOX4/NLRP3 signaling pathway to prevent apoptotic phenomena in a POF model [67]. HUCMSCs exosomal miRNA-29a (Figure 2(b)) [54] and HUCMSCs-derived exosomes [56,68] have promoted ovarian function, improved angiogenesis, developed folliculogenesis, and restored the estrous cycle through the Wnt/β-catenin, Hippo, and PI3K/AKT signaling pathways in POI-induced rodents, respectively.…”
Section: Exosome Therapymentioning
confidence: 99%
“…1). Many studies have found that MSCT significantly reduce the apoptosis of diseases-related tissue cells (Table 1), which is achieved by the activation of a variety of signaling pathways [13][14][15]. More interestingly, MSCs also alleviate diseases by promoting apoptosis in some cells, such as autoimmune diseases and tumors [16][17][18].…”
Section: Introductionmentioning
confidence: 99%